Heparan sulfate proteoglycan isoforms of the CD44 hyaluronan receptor induced in human inflammatory macrophages can function as paracrine regulators of fibroblast growth factor action. - Jones, M; Tussey, L; Athanasou, N; Jackson, D (2000)
The CD44 glycoprotein is expressed in multiple isoforms on a variety of cell types where it functions as a receptor for hyaluronan-mediated motility. Recently, interest has centered on CD44 heparan sulfate proteoglycan (HSPG) isoforms because of their potential to sequester heparin-binding growth factors and chemokines. Expression of these isoforms on ectodermal cells has recently been shown to regulate limb morphogenesis via presentation of fibroblast growth factor (FGF) 4/FGF 8 while expression on tumor cells was shown to sequester hepatocyte growth factor and promote tumor dissemination. To date, however, CD44 HSPG expression in tissue macrophages and lymphocytes has not been adequately investigated, despite the fact these cells actively synthesize growth factors and chemokines and indirect evidence that monocyte CD44 sequesters macrophage inflammatory protein-1beta. Here we show primary human monocytes rather than lymphocytes express CD44 HSPGs, but only following in vitro differentiation to macrophages or activation with the proinflammatory cytokine interleukin-1alpha or bacterial lipopolysaccharide. Furthermore, we show these isoforms are preferentially modified with heparan rather than chondroitin sulfate, bind the macrophage-derived growth factors FGF-2, vascular endothelial growth factor, and heparin-binding epidermal growth factor with varying affinities (K(d) 25-330 nM) and in the case of FGF-2, can stimulate productive binding to the high affinity tyrosine kinase FGF receptor 1 (FGFR1). In contrast, we find no evidence for significant binding to C-C chemokines. Last, we confirm by immunofluorescent antibody staining that inflamed synovial membrane macrophages express CD44 HSPGs and that expression is greatest in cells containing high FGF-2 levels. These results suggest a paracrine role for macrophage CD44 HSPG isoforms in the regulation of growth factor action during inflammation.